New Insights Into Causal Pathways Between the Pediatric Age-Related Physical Activity Decline and Loss of Control Eating: A Narrative Review and Proposed Conceptual Model - Mason, Tyler B.; Smith, Kathryn E.; Belcher, Britni R.; Dunton, Genevieve F.; Luo, Shan (Frontiers in Psychology, 2020)
Research consistently suggests that loss of control (LOC) eating in children and adolescents is a key factor contributing to pediatric obesity and eating disorders. However, causes of pediatric LOC eating are yet unclear, and there is a lack of longitudinal research investigating the developmental processes contributing to LOC eating and related outcomes in youth. Physical activity is an understudied behavior that declines during middle childhood to adolescence and may exert an influence in the development of LOC eating via its impact on executive functioning. While physical activity levels and executive functioning have been linked to regulation of eating, no research has examined the mechanistic processes by which these domains may together impact LOC eating during childhood and adolescence. In the current narrative review, a model is proposed that suggests how physical activity and executive functioning influence LOC eating and related outcomes during childhood and adolescence. This model has the potential to influence future theoretical models of pediatric LOC eating and guide future prevention and intervention efforts.